PERUBAHAN RELASI GENDER DAN SEKSUALITAS DALAM PROSTITUSI: KAJIAN FEMINISME BARAT DAN FEMINISME PASCAKOLONIAL - Humsona, Rahesli; Yuliani, Sri (UNIVERSITAS SEBELAS MARET (UNS), 2023)
The relationship between gender and sexuality in the prostitution industry has changed along with the development of information and communication technology. The purpose of this study was to determine the relation changes in particular between prostitutes, users, pimps and brokers. The perspectives used are western feminism and postcolonial feminism. The study used a qualitative method with a phenomenological approach. Sampling using purposive technique, data collection by observation, in-depth interviews and FGD. For the validity of the data, triangulation of sources and methods is used, while the data analysis uses an interactive model with components of data reduction, data display and conclusion drawing. The results of the study indicate that changes in gender relations and sexuality in the prostitution can be seen from the ability of women to control relations with men in production (earning income) which can be understood by Western feminism theory. Meanwhile, the inability of women can be seen in the consumption relationship (allocating income) which can be understood by Postcolonial feminism theory. Therefore, the theory of Western feminism and Postcolonial feminism does not need to be contradicted but is used according to the changing aspects of gender relations and sexuality in prostitution. Keywords: The Changed Of Relationship, Gender And Sexuality, Prostitution. AbstrakRelasi gender dan seksualitas dalam industri prostitusi mengalami perubahan seiring perkembangan teknologi informasi dan komunikasi. Tujuan penelitian ini untuk mengetahui perubahan relasi khususnya antara pelacur, pengguna, germo dan calo. Perspektif yang digunakan adalah feminisme barat dan feminisme pascakolonial. Penelitian menggunakan metode kualitatif dengan pendekatan fenomenologi. Pengambilan sampel menggunakan teknik purposif, pengambilan data dengan observasi, wawancara mendalam dan FGD. Untuk validitas data menggunakan triangulasi sumber dan metode, sedang analisis data menggunakan model interaktif dengan komponen reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa perubahan relasi gender dan seksualitas dalam prostitusi nampak dari kemampuan perempuan untuk mengendalikan relasi dengan laki-laki dalam produksi (memperoleh pendapatan) yang dapat dipahami dengan teori feminisme barat. Sedang ketidakmampuan perempuan nampak dalam relasi berkonsumsi (mengalokasikan pendapatan) yang dapat dipahami dengan teori feminisme pascakolonial. Oleh karena itu teori feminisme Barat dan feminisme pascakolonial tidak perlu dipertentangkan melainkan dimanfaatkan sesuai dengan aspek perubahan relasi gender dan seksualitas dalam prostitusi. Kata Kunci: Perubahan Relasi, Gender Dan Seksulitas, Prostitusi.